Developing a valid and reliable quality design criterion rubric to evaluate online courses: a case of three entrepreneurial online short courses at the University of the Witwatersrand - Makda, Fatima (My University, 2019)
Online learning has been identified as a growing area in the education sector and many educational institutions are expanding their offering of online courses. When designing online courses, there are several design considerations and decisions that need to be made. Despite the development of various instructional design literature and the potential of online courses to support learning, there exists a gap between theoretical knowledge (theory) and practice (reality). The objective of the current research study is to determine the effectiveness of the design of online courses for teaching and learning, and what designers and instructors of online learning environments should collectively consider in terms of the quality of the design for online courses. The current study found the dimensions (1) course information, course structure and course organisation, (2) interaction and communication, (3) multimedia design, (4) assessment and feedback, and (5) effective use of technology of online courses to be important contributors towards the quality design of online courses. Using these dimensions, a valid and reliable evaluation instrument was developed – a rubric. In the current study, the rubric is used as an evaluation tool to evaluate three online short courses at a university level. The current study uses a quantitative instrument design methodology as it involves measuring by scoring various criterion on the developed rubric. These scores were measured and analysed using simple descriptive statistics. Qualitative descriptive evaluations of the online short courses were also done. Both the quantitative and qualitative aspects of the online course analysis were integrated to ascertain a summative conclusion of the three online courses and whether the rubric, as a design framework, needed further improvement or not. The current study provides a contribution towards literature by advancing the development of best practices in terms of quality design and evaluation of online courses. The rubric offers a framework to determine what components contribute towards quality design in online courses. This framework contains a set of benchmarks that will assist instructors and course designers in one of two ways; (1) as a self-evaluation tool for an online course thus advising the appropriate stakeholder on how to revise their current online course, and (2) as a best practice guideline to design a new course within the online environment.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, in 50% fulfilment of the requirements for the degree of Master of Education (in the field of Educational Technology).
Keywords: Internet in higher education; Web-based instruction; Open learning